2011
DOI: 10.1088/0957-4484/22/15/155602
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature sol–gel-derived nanosilver-embedded silane coating as biofilm inhibitor

Abstract: Silver nanocomposite coatings are prepared by the sol-gel method for the prevention of biofilm formation on the surface of medical implanted devices. High-temperature processing of such coatings can lead to diffusion of nanosilver and reduce the amount of available silver particles for long-term effects. Using a low-temperature sol-gel method, we have successfully prepared silane-based matrices, phenyltriethoxysilane (PhTEOS), containing different amounts of Ag nanoparticles. The incorporation of a silver salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A similar silver release is described in the literature for most silver-based nanocomposite polymeric coatings [41][42][43]. Dissolution of silver in aqueous solutions is dependent on electrolyte type and concentration, pH, temperature and the presence of dissolved oxygen [44][45][46][47][48]; in particular, the presence of electrolytes in aqueous solution diminishes the electrostatic energy barrier to nanoparticle aggregation [45].…”
Section: Durability Of the Antibacterial Properties Of Chitlac-nag-comentioning
confidence: 55%
“…A similar silver release is described in the literature for most silver-based nanocomposite polymeric coatings [41][42][43]. Dissolution of silver in aqueous solutions is dependent on electrolyte type and concentration, pH, temperature and the presence of dissolved oxygen [44][45][46][47][48]; in particular, the presence of electrolytes in aqueous solution diminishes the electrostatic energy barrier to nanoparticle aggregation [45].…”
Section: Durability Of the Antibacterial Properties Of Chitlac-nag-comentioning
confidence: 55%
“…38 The high resolution Ag 3d spectrum could be deconvoluted including three additional peaks at binding energies of 367.7, 368.8, and 374.2 eV, thereby indicating the presence of small proportions of AgO, and Ag 2 O along with metallic silver. 39,40 To verify the presence of an oxide layer on the immobilized AgNPs, a high-resolution O 1s spectrum was further analysed. The deconvoluted O 1s spectrum appeared to be more complex.…”
Section: Characterization Studiesmentioning
confidence: 99%
“…; Babapour et al . ; Naik and Kowshik ), and the anti‐QS activity of this traditionally used bioactive agent with potential in food preservation has not yet been explored. This study evaluates the anti‐QS activity of silver entrapped in a titanium dioxide (TiO 2 ) matrix.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of literature about the antimicrobial activity of various forms of silver and silver composites and their mechanism of action (Panacek et al 2006;Kim et al 2007;Lara et al 2011;Brandt et al 2012;Naik et al 2013). However, only few studies have reported antibiofilm activity of silver and silver-based compounds (Stobie et al 2008;Kalishwaralal et al 2010;Babapour et al 2011;Naik and Kowshik 2014), and the anti-QS activity of this traditionally used bioactive agent with potential in food preservation has not yet been explored. This study evaluates the anti-QS activity of silver entrapped in a titanium dioxide (TiO 2 ) matrix.…”
Section: Introductionmentioning
confidence: 99%